Investigations on Temperature Effects and Germ Recovery for Solar Water Disinfection (SODIS) - Sift, Michael; Wagner, Sophia; Hessling, Martin (International Journal of Applied Sciences and Biotechnology, 2017)
In many developing countries no infrastructure for providing people with microbiological safe drinking water exists. This demands for decentralized water disinfection that is inexpensive and requires no consumables. The casualties are often recommended the application of SODIS for drinking water treatment. There are numerous scientific studies on this disinfection method, which however are still leaving questions on the mode of functioning which is often reduced to the effect caused by the UV part of the solar radiation and there is almost no discussion in the literature what happens to the disinfected water after the SODIS treatment.In this paper disinfection experiments with Escherichia coli in isotonic saline solutions and real surface water are performed for a set of realistic conditions for UVA irradiation and for heating but separated from each other. The results confirm that SODIS is based on the combined effect of UVA radiation and increased temperature. Further experiments lead to the recommendation that once disinfected water should be consumed without a large delay, otherwise the germ concentration rises again.Int J Appl Sci Biotechnol, Vol 4(4): 430-435